2022
DOI: 10.21203/rs.3.rs-2175987/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stromal-tumor amplifying STC1-Notch1 feedforward signal promotes the stemness of hepatocellular carcinoma

Abstract: Background Cancer associated fibroblasts (CAFs), an important component of the tumor microenvironment (TME), play crucial roles in tumor stemness. Stanniocalcin-1 (STC1) was found secreted by CAFs in various cancers, but its main source and its role in hepatocellular carcinoma (HCC) was still unclear. Methods The serum and intracellular expression levels of STC1 were detected by ELISA and western blot. The role of CAFs-derived STC1 in HCC stemness was probed by sphere formation, sorafenib resistance, colony … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Stanniocalcin 1 (STC1), which was first identified in bony fish, is a disulfide-bound glycoprotein hormone involved in plasma calcium and phosphate homeostasis (7). Previous studies have reported that STC1 functions as an oncogene in various types of cancer; for example, STC1 has been reported to promote metastasis in ovarian cancer and cancer-associated fibroblast-derived STC1 can promote stemness in hepatocellular carcinoma (8,9). Notably, STC1 promotes the growth and metastasis of breast cancer tumors (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Stanniocalcin 1 (STC1), which was first identified in bony fish, is a disulfide-bound glycoprotein hormone involved in plasma calcium and phosphate homeostasis (7). Previous studies have reported that STC1 functions as an oncogene in various types of cancer; for example, STC1 has been reported to promote metastasis in ovarian cancer and cancer-associated fibroblast-derived STC1 can promote stemness in hepatocellular carcinoma (8,9). Notably, STC1 promotes the growth and metastasis of breast cancer tumors (10,11).…”
Section: Introductionmentioning
confidence: 99%